The design of an improved efficiency lavender harvester - Dimitriadis, Christos I. (Cranfield University, 2005)
The introduction of new methods to solve a specific task was always the ignition for the human mind to find new solutions. Considering the new demands in mechanical lavender harvest for oil production a novel harvester has been developed employing the stripping technique (Klinner et al., 1986a,b,c,d; Hobson et al., 1988) developed for the harv~~ting of cereals. The harvester works in a unique way for this crop by removing the flower :~eads_ in the field, leaving the majority of the stems intact. Convention~! harvesting methods such as hand harvest and mechanical harvest using a . cutting mechanism collects both the flower head and a cut length of the stem. This was found to be an inefficient method for the harvest of lavender because most of the oil produced by the plant (97.5 % by weight - Venskutonis, 1997) is located on the flower. Also using these methods the amount of stem collected increases the transportation and the distillation costs, generates more demanding designs, and removes the stem from the field that could otherwise be left as a natural nutrient. Taking this into account and that the British Pharmacopoeia directs that in making the most refined lavender oil (for medicinal use) it should be distilled from the flowers after they have been separated (stripped) from their stalks (Grieve, 2001) the proposed harvesting technique is ideal for the production of high quality lavender oil.